2023
DOI: 10.1002/maco.202213496
|View full text |Cite
|
Sign up to set email alerts
|

The effect of the MCrAlY composition and aluminizing cycle upon the microstructure and hot corrosion resistance of the over‐aluminized MCrAlY coating on IN738LC alloy substrate

Abstract: The aluminizing behavior of high-velocity oxy-fuel sprayed CoNiCrAlY, or NiCoCrAlY-coated IN738LC alloy has been investigated via asingle or two-step pack cementation aluminizing processes. The microstructural study showed that a more desirable low aluminum-containing MCrAlY coating is obtained through single-step aluminizing. The resultant over-aluminized coating microstructure consisted of the Co-containing beta-NiAl in the aluminide top layer and the Ni−Co−Cr-based austenitic gamma solid solution matrix dec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…It has been reported that the NiAl coatings doped with zirconia [18][19][20] and hafnium [21] also reduce the oxidation rate of nickel-based superalloys since the addition of these elements leads to the formation of stable oxides, inhibiting aluminum depletion. Other significant studies report that a functional NiCoCrAlY coating improves the hot-corrosion resistance of Inconel 738L exposed to air for 100 h at 700 • C [22]. It is worth mentioning that aluminide coatings also improve the high-temperature corrosion resistance of Inconel 718 in a salty environment [23].…”
Section: Pack Cementation (Pc) and Above The Pack/vapor-phase Alumini...mentioning
confidence: 96%
See 3 more Smart Citations
“…It has been reported that the NiAl coatings doped with zirconia [18][19][20] and hafnium [21] also reduce the oxidation rate of nickel-based superalloys since the addition of these elements leads to the formation of stable oxides, inhibiting aluminum depletion. Other significant studies report that a functional NiCoCrAlY coating improves the hot-corrosion resistance of Inconel 738L exposed to air for 100 h at 700 • C [22]. It is worth mentioning that aluminide coatings also improve the high-temperature corrosion resistance of Inconel 718 in a salty environment [23].…”
Section: Pack Cementation (Pc) and Above The Pack/vapor-phase Alumini...mentioning
confidence: 96%
“…NiAl + Hf/PC Formed HfO2 acts as a diffusion barrier to prevent inter-diffusion during cyclic oxidation; the surface rumpling extent is much relieved due to a slower Al depletion rate and higher creep resistance by Hf addition [21] Inconel 738L NiCoCrAlY/PC Improved hot-corrosion resistance at 700 °C [22] Inconel 718 NiAl/PC Aluminized surface reduced the hot corrosion by 50% at 700 °C in an NaCl environment [23] Nickel Ni2Al3/PC Ultrafine-grained Ni2Al3 coating significantly enhances the oxidation resistance in air at 900 °C [24]…”
Section: Nickelmentioning
confidence: 99%
See 2 more Smart Citations